2021
DOI: 10.1039/d0ra09756j
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive and rapid responding humidity sensors based on silver catalyzed Ag2S–TiO2 quantum dots prepared by SILAR

Abstract: Ag2S@TiO2 films was made as humidity sensors by SILAR method. The heterojunction and nano-silver improve the electrons transfer and increase the response and reaction rate. It also provides high gas selectivity to avoid effect of air pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The matrix is later used in the fabrication of the bimodal sensor. From the TH-matrix data, it's found that the sample has a highest sensitivity of 4.4%/RH% under the temperature of 30 °C, which is 3 times more than previously reported resistive moisture sensors, which have their sensitivities in the range of 1–2%/RH% at maximum [ [38] , [39] , [40] , [41] ]. Detailed comparison is shown in Table S2 .…”
Section: Resultsmentioning
confidence: 72%
“…The matrix is later used in the fabrication of the bimodal sensor. From the TH-matrix data, it's found that the sample has a highest sensitivity of 4.4%/RH% under the temperature of 30 °C, which is 3 times more than previously reported resistive moisture sensors, which have their sensitivities in the range of 1–2%/RH% at maximum [ [38] , [39] , [40] , [41] ]. Detailed comparison is shown in Table S2 .…”
Section: Resultsmentioning
confidence: 72%
“…As the baseline resistance decreased, the consumption of O − reduced its reactivity with the target gas, resulting in a decline in sensor response. In addition, according to the reported literature, the resistance value of Ag 2 S is greatly affected by water molecules and can be used as a sensitive material for humidity sensors [ 45 , 46 ], which is also a reason why the ACS-3 sensor was significantly affected by humidity. To mitigate the effects of humidity in practical applications, humidity compensation can be implemented to minimize the disparities in sensor response under varying humidity conditions.…”
Section: Resultsmentioning
confidence: 99%
“…00-094-0510) [11][12][13][14][15]. The average crystallite size was measured by the Debye-Scherrer formula and found to be 25.7 nm [16]. The main crystal plane of isotropic GaOOH material (JCPDS No.…”
Section: Resultsmentioning
confidence: 99%